The BioRow™ Catch Training System - Kleshnev, V. (Rowing Biomechanics Newsletter, 2016)
Presented is the new BioRow™ Catch Training System (BRCTS) has been recently developed, and was presented at the World Cup Regatta in Lucerne (Fig.1). The system is a new tool for quick and easy learning and stabilisation of an effective catch technique and proper rowing style.